THE EVOLUTION OF LANGUAGE TEACHING APPROACHES: FROM TRADITIONAL METHODS TO TECHNOLOGY-BASED LEARNING - Imelda Imelda; Ignatius Septo Pramesworo; Fety Surfaifel (Review of International Journal Education and School Leadership, 2025)
The evolution of language teaching approaches has undergone a significant shift from traditional methods towards technology-based learning. Traditional methods such as grammar-translation and audio-lingual focus on memorising grammar rules and mastering vocabulary, but are often less effective in improving practical communication skills. Technological developments provide solutions to these limitations through the integration of digital tools such as learning apps, interactive multimedia, and technology-based simulations. This technology-based approach offers varied content, personalisation of learning materials, and flexibility in time and place of learning. This evolution reflects a response to the evolving needs of learners and the potential of technology to create more inclusive, engaging and effective language learning in the modern digital era.